From State Monopoly to Battlefield: A Historical Analysis of Media, Power, and Conflict in Libya (1952–Present) - Ibrahim Ali Omer (MD Research Center, 2026)
The evolution of Libyan media from a state-controlled system to a weaponized landscape in the post-2011 period reflects the broader transformation of political power in the country, yet existing scholarship has largely failed to provide a comprehensive historical analysis connecting media development to dynamics of state control, conflict, and external intervention. This study aims to analyze how political power and social conflict have shaped the evolution of media in Libya from independence in 1952 to the present. Employing a qualitative historical-analytical approach with thematic analysis of academic literature, historical documents, and media reports, the study traces media transformation across three political eras: the Monarchy, the Gaddafi regime, and the post-2011 period. The findings reveal that Libyan media evolved from a state-controlled instrument under authoritarian rule to a fragmented and weaponized environment where various TV channels serve as propaganda tools for warring factions, as evidenced by 1,070 documented ethical violations across 12 channels. The study concludes that media in Libya have never been autonomous but have always mirrored the power structures underlying them, and that sustainable media reform requires the establishment of independent regulatory bodies, protection of journalists, and integration with broader political stabilization efforts.